Factores de riesgo criminógenos en población penitenciaria extramuros del establecimiento medio libre del Instituto Nacional Penitenciario Iquitos 2017 al 2019 - Barrera Mozombite, Mario Alfredo (2023)
The present research concerns a true experimental design, of quantitative type. The study population were released for the crimes of Aggravated Robbery, Illicit Drug Trafficking, Aggravated Theft and Fraud (180 people). The sample consists of 54 people; The survey technique and a questionnaire were used as an instrument, which had a validity of 80%. The respondents confirm the basic premise that the personal decision is the determining element in the criminal commission, since 96.30% consider themselves responsible for the crime they committed; However, there are conditioning elements, which we consider endogenous and exogenous criminogenic factors, that favor the criminal commission. Among the endogenous criminogenic factors are aspects related to their personality and behavior, in which 70.37% consider that impulsivity or some negative internal force prompted them to commit a crime; we also have exogenous criminogenic factors (socio-family and socio-economic aspects), As explained: (i) 72.22% indicate that the difficulties they experienced at home (episodes of physical, verbal violence, etc.) and lack of parental control affected their behavior; (ii) 70.37% affirm that they did not have a good formation in values and principles in their home and the School; (iii) 64.81 considers that bad friends and the environment where he grew up and developed influenced their criminal behavior, (iv) 70.37% consider that poverty and economic scarcity drove them to commit a crime and (v) 74.07% indicated that they come from a poor family, with economic difficulties. In relation to the activities of the Free Environment program of the National Penitentiary Institute (INPE), 68.52% state that it was very useful and at the same time, 92.60% affirm that these programs need more support from the government and society. Finally, 74.07% consider that the hardening of penalties contributes to the fight against crime. Therefore, the hypothesis raised in this research work that there are criminogenic factors in the population outside the walls of the INPE Free Environment program is accepted.